Constitutional variants in POT1, TERF2IP, and ACD genes in patients with melanoma in the Polish population. Issue 6 (November 2020) - Malińska, Karolina; Deptuła, Jakub; Rogoża-Janiszewska, Emilia; Górski, Bohdan; Scott, Rodney; Rudnicka, Helena; Kashyap, Aniruddh; Domagała, Paweł; Hybiak, Jolanta; Masojć, Bartłomiej; Cybulski, Cezary; Kram, Andrzej; et al.
Abstract : Evaluation of the prevalence of POT1, ACD, and TERF2IP mutations among Polish melanoma patients. A cohort of 60 patients from melanoma-prone families, 1500 unselected cases and 1500 controls were genotyped. Methodology included Sanger sequencing, in-silico software predilection, and TaqMan assays. We identified three nonsynonymous variants: POT1 c.903 G>T; TERF2IP c.970 A>G; and ACD c.1544 T>C and a splice site variant ACD c.645 G>A. The c.903 G>T was predicted to be pathogenic according to PolyPhen-2, benign according to Mutation Taster, PROVEAN, AGVGD, and SIFT. The c.645 G>A was defined as disease caused by Mutation Taster and Human Splicing Finder and as variant of unknown significance by ClinVar. The other detected variants were described as benign. The c.903 G>T variant was present in two unselected cases and one control [ P = 0.57, odds ratio (OR) = 2.00]; the c.645 G>A variant was not detected among the unselected cases and the controls; the c.970 A>G variant was present in 110 cases and 133 controls ( P = 0.14, OR = 0.81); the c.1544 T>C variant was present in 687 cases and 642 controls ( P = 0.11, OR = 1.07). We found no loss of heterozygosity of the c.903 G>T, c.970 A>G, and c.645 G>A variants. C.645 G>A variant had no effect on splicing or expression. The changes in POT1 c.903 G>T and ACD c.645 G>A can be classified as rare variants of unknown significance, the other variants appear to be polymorphisms. Germline mutations in POT1, ACD, and TERF2IP are infrequent among Polish melanoma patients.